2010
DOI: 10.1080/22201173.2010.10872678
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between spinal column length and the spread of subarachnoid hyperbaric bupivacaine in the term parturient

Abstract: Background: Anaesthetists frequently tailor the subarachnoid local anaesthetic dosage according to parturient height to achieve sensory blockade up to the T4 dermatome for lower segment Caesarean sections (LSCSs). Studies that have been conducted have demonstrated that height does not affect the spread of subarachnoid hyperbaric bupivacaine. This study aimed to nd the correlation between the spinal column length of term parturients and the highest level of sensory blockade after spinal anaesthesia. Methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Furthermore, in this study there was no significant association between vertebral column and cephalad spread of spinal anesthesia. Similar to this study, Wan Rahiza et al [28] spinal column length and the spread of anaesthesia was not significantly correlated. However many studies showed contrasting reports as that of the present study.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, in this study there was no significant association between vertebral column and cephalad spread of spinal anesthesia. Similar to this study, Wan Rahiza et al [28] spinal column length and the spread of anaesthesia was not significantly correlated. However many studies showed contrasting reports as that of the present study.…”
Section: Discussionsupporting
confidence: 87%
“…Chanimov M et al 14 in their study found a significant correlation between vertebral column length (C7 to iliac crest) and highest sensory level. Rahiza WW et al 15 in a study of the relationship between spinal column length and sensory spread, spinal column length (C7 to SH) showed no correlation with the highest level of sensory blockade achieved. We have found a positive correlation between HSWR and highest sensory level achieved, whereas VCL, height, weight, BMI had no effect on sensory level.…”
Section: Discussionmentioning
confidence: 93%
“…The mean vertebral column length in our study was 54.99 ± 4.59, which showed a negative correlation with the cephalad spread of sensory level of anesthesia, although it was not statistically significant, which is similar to the study conducted by Wan Rahiza et al . [ 13 ] where no significant association was found between VCL and cephalad spread of anesthesia. However, many other studies like that of Zhou et al .…”
Section: Discussionmentioning
confidence: 99%